2008
DOI: 10.1159/000118760
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal expression and localization of aphidicolin-induced fragile sites in the standard karyotype of river buffalo <i>(Bubalus bubalis)</i>

Abstract: The present study reports on the chromosomal expression and localization of aphidicolin-induced fragile sites in the standard karyotype of river buffalo (Bubalus bubalis, 2n = 50) with the aim of establishing a ‘fragile site map’ of the species. Totally, 400 aphidicolin-induced breakages were analyzed from eight young and clinically healthy animals, four males and four females; these breakages were localized in 106 RBG-negative chromosome bands or at the band-interband regions. The number of breakages per chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
1
9
1
Order By: Relevance
“…There is great interest in fragile sites, as they show a nonlinear distribution throughout genomes and frequently overlap the so-called evolutionary breakpoints Ruiz-Herrera et al, 2006]. The localization of the WWOX gene obtained in this study is in good agreement with breakpoints induced by aphidicolin treatment for Bos taurus , specifically at BTA18q12 [Rodrigues et al, 2002], and to a minor extent with the data reported in a similar study on Bubalus bubalis where the closest aphidicolin-induced fragile site is mapped to BBU18q21 [Nicodemo et al, 2008]. However, it should be pointed out that the conservation of fragile sites seems more significant than that suggested by cytogenetic approaches, as clearly shown by studies that extended the comparison between mouse and man to other speciesincluding domestic animals and cattle -and exploited genome assemblies as an additional and more powerful tool for analysis [Murphy et al, 2005].…”
Section: Fish Mapping Of Wwox In Cattle River Buffalo Sheep and Goatsupporting
confidence: 89%
See 1 more Smart Citation
“…There is great interest in fragile sites, as they show a nonlinear distribution throughout genomes and frequently overlap the so-called evolutionary breakpoints Ruiz-Herrera et al, 2006]. The localization of the WWOX gene obtained in this study is in good agreement with breakpoints induced by aphidicolin treatment for Bos taurus , specifically at BTA18q12 [Rodrigues et al, 2002], and to a minor extent with the data reported in a similar study on Bubalus bubalis where the closest aphidicolin-induced fragile site is mapped to BBU18q21 [Nicodemo et al, 2008]. However, it should be pointed out that the conservation of fragile sites seems more significant than that suggested by cytogenetic approaches, as clearly shown by studies that extended the comparison between mouse and man to other speciesincluding domestic animals and cattle -and exploited genome assemblies as an additional and more powerful tool for analysis [Murphy et al, 2005].…”
Section: Fish Mapping Of Wwox In Cattle River Buffalo Sheep and Goatsupporting
confidence: 89%
“…In domestic animals fragile sites have not received much attention, although published data suggest the importance of developing species-specific genome maps for fragile sites as a tool for studies of karyotype evolution, comparative genomics and mutational cytogenetics [Rodriguez et al, 2002;Nicodemo et al, 2008]. We have focused our attention on the isolation and annotation in the bovine genome of genes known to map at common fragile sites exploiting their high conservation and using a comparative approach.…”
mentioning
confidence: 99%
“…Fragile sites have been identified in the river buffalo karyotype ( Bubalus bubalis) . The most recent efforts were described in conjunction with high resolution karyotype s [Pires et al, 1998;Mahrous and Ahmed, 2000;Sanghamitra et al, 2004;Ahmed, 2005;Nicodemo et al, 2007Nicodemo et al, , 2008. Based on the buffalo cytogenetic map [Iannuzzi et al, 2003] and the most recent fragile site map, some putative orthologous fragile sites in buffalo corresponding to other mammals are included in table 1 .…”
Section: Bovidaementioning
confidence: 99%
“…Based on the buffalo cytogenetic map [Iannuzzi et al, 2003] and the most recent fragile site map, some putative orthologous fragile sites in buffalo corresponding to other mammals are included in table 1 . Despite their close chromosome-banding homology with cattle, results from buffalo [Nicodemo et al, 2008] and cattle [Rodriguez et al, 2002] were quite different. Several bovine breakpoints orthologous to the most common buffalo fragile sites were apparently observed by Rodriguez and colleagues [2002], but did not reach the significance required for classification of fragile sites.…”
Section: Bovidaementioning
confidence: 99%
See 1 more Smart Citation